Acute exposure of zebrafish embryo (Danio rerio) to flutolanil reveals its developmental mechanism of toxicity via disrupting the thyroid system and metabolism. (November 2018) - Teng, Miaomiao; Zhu, Wentao; Wang, Dezhen; Yan, Jin; Qi, Suzhen; Song, Min; Wang, Chengju
Abstract: Flutolanil, an amide fungicide, had been detected frequently in aquatic environments; it is thus potentially a great risk to aquatic organisms and human health. Therefore, we investigated the developmental toxicity and the potential mechanism of thyroid endocrine disruption induced by flutolanil based on 1 H NMR metabolomics analysis using a zebrafish model. Hatching of zebrafish embryo exposed to flutolanil was inhibited at 72 hpf (hour post-fertilization) and survival and body length at 96 hpf. In addition, increased teratogenic effects on embryos were observed, including pericardial edema, spine deformation, and tail malformation. Furthermore, flutolanil induced slower heartbeat and larger pericardial area in the treated groups than control group. Transcription levels of TRH, TSHR, TPO, Dio1, TRα, and UGT1ab were significantly altered after flutolanil exposure. Metabolomics analysis further indicated that flutolanil induced alterations of energy, amino acids, nucleotide, lipids, and fatty acid metabolism. Our study also indicated that flutolanil exposure led to alterations of endogenous metabolites, which induced the thyroid endocrine disruption in zebrafish. Ultimately, embryonic developmental toxicity was caused by flutolanil. Graphical abstract: Image 1 Highlights: Flutolanil induced cardiac effect, spine and tail deformation in zebrafish embryos. Flutolanil exposure induced thyroid endocrine disruption in zebrafish embryos. Flutolanil exposure increased the level of thyroid hormones. Flutolanil exposure altered genes expression in the HPT axis in zebrafish embryos. Metabolism pathways disturbance in embryos were observed after flutolanil exposure. Abstract : Flutolanil exposure led to alterations of endogenous metabolites, which induced developmental toxicity and thyroid disruption in zebrafish.